Effects of Viscous Dissipation on Mixed Convection Boundary Layer Flow Past a Vertical Moving Plate in a Nanofluid - Muhammad Khairul Anuar, Mohamed; Mohd Zuki, Salleh; Anuar, Ishak (Semarak Ilmu Publishing, 2020)
Adaptation from the thermal management applied in modern engine cooling system and central processing unit (CPU) in performance computer devices, present study solved the problem of steady mixed convection boundary layer flow and heat transfer on a moving vertical plate in a nanofluid with the presence of viscous dissipation and constant wall temperature. The mathematical model which is in non-linear partial differential equations is solved numerically by similarity transformation approach with the Keller-box method. The characteristics and effects of pertinent parameters considered which are Prandtl number, Lewis number, Eckert number, Brownian motion parameter, thermophoresis parameter, mixed convection parameter, concentration mixed convection parameter and plate velocity parameter are analyzed and discussed. In conclusion, there exist dual solutions in opposing flow for moving parameter range 0.18 0.48.    Further, the increase of mixed convection parameter in assisting flow results to the increase in the Nusselt number and skin friction coefficient.